The Impact of Information Uncertainty on Stock Performance During the 2008-2009 Financial Crisis - Allen, Arthur; Zhang, Wei (Journal of Accounting and Finance, 2023)
We investigate the impact of information uncertainty on stock performance during the 2008-2009 financial crisis. We document that firms with more information uncertainty suffered a greater stock price drop during the period of market-wide price declines. In contrast, the negative effect of information uncertainty on stock returns was absent during the market-reversal or pseudo-drop period. In addition, during the reversal period, firms with forecast dispersion in the top tercile (or quartile) had more positive returns than those with lower forecast dispersion. We contribute to the literature by testing the relationship between information uncertainty and firm returns in the special setting of the most recent financial crisis and providing initial evidence that firm-specific information uncertainty amplified stock price fluctuations during the financial crisis.